2015
DOI: 10.7852/jses.2015.53.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation of silk proteins obtained from Bombyx mori silkworm varieties

Abstract: It is known that silk protein supports effectively proliferation of cell such as insect cell and hybridoma cell. Although there are many varieties of Bombyx mori silkworm, the effect of silkworm varieties on cell proliferation has not been considered in detail. We studied that characteristics of silk cocoon obtained from Baegokjam, Kumokjam, Daeseongjam silkworm varieties and whether silk protein affected cell proliferation or not. Silk sericin was prepared under high temperature and high pressure condition. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Particularly, Heuros of Australia is focusing on synthesizing recombinant proteins to develop culture media that do not contain antibiotics, hormones, and serum [ 21 ]. However, in the case of Korea, both FBS-based and serum-free media rely mostly on imports; therefore, the development of its own product is a priority for Korea [ 22 ]. For the industrialization of cultivated meat, persistent mass production is essential; therefore, cultivating meat in a three-dimensional (3D) space instead of a two-dimensional (2D) space can help further increase production because cells grow better when attached to a surface [ 23 ].…”
Section: Summary Of the Development Of Cultivated Meat Technologiesmentioning
confidence: 99%
“…Particularly, Heuros of Australia is focusing on synthesizing recombinant proteins to develop culture media that do not contain antibiotics, hormones, and serum [ 21 ]. However, in the case of Korea, both FBS-based and serum-free media rely mostly on imports; therefore, the development of its own product is a priority for Korea [ 22 ]. For the industrialization of cultivated meat, persistent mass production is essential; therefore, cultivating meat in a three-dimensional (3D) space instead of a two-dimensional (2D) space can help further increase production because cells grow better when attached to a surface [ 23 ].…”
Section: Summary Of the Development Of Cultivated Meat Technologiesmentioning
confidence: 99%
“…Also, silk fibroin was recognized by the US Food and Drug Administration (FDA) as a biomaterial in 1993 [32]. Previous studies have shown that silk protein (sericin and fibroin) treatment is effective in cell proliferation and that there is a significant difference between silkworm varieties [33]. Sericin and fibroin from silkworm cocoons of five varieties were made to observe FBS substitution ability of silk proteins.…”
Section: Effect Of Silk Sericin and Fibroinmentioning
confidence: 99%
“…The annual plant P. tinctorium has long been employed in the medical and dye industries (Cooksey, 2007;Hirota et al, 2014). It is also often used in many nations, particularly Korea and Japan, for traditional fabric staining as a source of blue color (Chung et al, 2005;Hirota et al, 2016). A substance called indigo, which was discovered from P. tinctorium, is widely used in traditional Chinese medicine and as a natural color in denim manufacturing (Kukuła-Koch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%